You are on page 1of 8

Fuzzy Modelling Using Sector Non-linearity Principle

For the sake of simplicity, consider the following SISO nonlinear system:

𝑥̇ = 𝑓(𝑥)𝑥 + 𝑔(𝑥)𝑚

Where

𝑥 ∈ [−𝑑, 𝑑]

𝑓 ∈ [𝑓, 𝑓]

𝑔 ∈ [𝑔, 𝑔]

and 𝑓 = min 𝑓(𝑥) , 𝑓 = max 𝑓(𝑥), 𝑔 = min 𝑔(𝑥), 𝑔 = max 𝑔(𝑥)


|𝑥|<𝑑 |𝑥|<𝑑 |𝑥|<𝑑 |𝑥|<𝑑

Then the T-S fuzzy model is given by: 𝑀𝑓2 𝑀𝑓1 𝑀𝑔2 𝑀𝑔1

R1: If f(x) is Mf1 and g(x) is Mg1 Then 𝑥̇ = 𝑓𝑥 + 𝑔𝑚


R2: If f(x) is Mf1 and g(x) is Mg2 Then 𝑥̇ = 𝑓𝑥 + 𝑔𝑚
𝑓 𝑓 𝑔
R3: If f(x) is Mf2 and g(x) is Mg1 Then 𝑥̇ = 𝑓𝑥 + 𝑔𝑚 𝑔
R4: If f(x) is Mf2 and g(x) is Mg2 Then 𝑥̇ = 𝑓𝑥 + 𝑔𝑚
Where, Mf1 , Mf2 , Mg1 , Mg2 is given by

𝑓−𝑓 𝑓−𝑓 𝑔−𝑔 𝑔−𝑔


𝑀𝑓1 = , 𝑀𝑓2 = 1 − 𝑀𝑓1 = and 𝑀𝑔1 = 𝑔−𝑔 , 𝑀𝑔2 = 1 − 𝑀𝑔1 = 𝑔−𝑔
𝑓−𝑓 𝑓−𝑓

1
𝜇𝑅1 = 𝑀𝑓1 ∙ 𝑀𝑔1

𝜇𝑅2 = 𝑀𝑓1 ∙ 𝑀𝑔2

𝜇𝑅3 = 𝑀𝑓2 ∙ 𝑀𝑔1

𝜇𝑅4 = 𝑀𝑓2 ∙ 𝑀𝑔2

Then the basis functions can be calculated as:


𝜇𝑅1 𝜇𝑅1 𝜇𝑅1
ℎ1 = 𝑟 = = = 𝑀𝑓1 ∙ 𝑀𝑔1
∑1 𝜇𝑅𝑖 𝜇𝑅1 + 𝜇𝑅2 + 𝜇𝑅3 + 𝜇𝑅4 1
𝜇𝑅2 𝜇𝑅2
ℎ2 = 𝑟 = = 𝑀𝑓1 ∙ 𝑀𝑔2
∑1 𝜇𝑅𝑖 1
𝜇𝑅3 𝜇𝑅3
ℎ3 = 𝑟 = = 𝑀𝑓2 ∙ 𝑀𝑔1
∑1 𝜇𝑅𝑖 1
𝜇𝑅4 𝜇𝑅4
ℎ4 = = = 𝑀𝑓2 ∙ 𝑀𝑔2
∑𝑟1 𝜇𝑅𝑖 1

Note that:

ℎ1 + ℎ2 + ℎ3 + ℎ4 = 𝑀𝑓1 (𝑀𝑔1 ∙ 𝑀𝑔2 ) + 𝑀𝑓2 (𝑀𝑔1 ∙ 𝑀𝑔2 ) = 𝑀𝑓1 + 𝑀𝑓2 = 1

Using the T-S defuzzification results in blending of the four rules.

𝑥̇ = (ℎ1 𝑓 + ℎ2 𝑓 + ℎ3 𝑓 + ℎ4 𝑓)𝑥 + (ℎ1 𝑔 + ℎ2 𝑔 + ℎ3 𝑔 + ℎ4 𝑔)𝑚

The last equation represents exactly the original model.

Consider the term

ℎ1 𝑓 + ℎ2 𝑓 + ℎ3 𝑓 + ℎ4 𝑓 = (ℎ1 + ℎ2 )𝑓 + (ℎ3 + ℎ4 )𝑓

= 𝑀𝑓1 𝑓 + 𝑀𝑓2 𝑓

𝑓−𝑓 𝑓−𝑓
= 𝑓+ 𝑓=𝑓
𝑓−𝑓 𝑓−𝑓

Then

𝑥̇ = (ℎ1 𝑓 + ℎ2 𝑓 + ℎ3 𝑓 + ℎ4 𝑓)𝑥 + (ℎ1 𝑔 + ℎ2 𝑔 + ℎ3 𝑔 + ℎ4 𝑔)𝑚 = 𝑓(𝑥)𝑥 + 𝑔(𝑥)𝑚

Example 1

Let 𝑥̇ = −𝑥 3 , 𝑥 ∈ [−𝑑, 𝑑]

Then 𝑓 = −𝑥 2, and 𝑓 = −𝑑2 , 𝑓=0

2
𝑓−𝑓 −𝑥 2 +𝑑 2 𝑓−𝑓 𝑥2
𝑀𝑓1 = = and 𝑀𝑓2 = 1 − 𝑀𝑓1 = =
𝑓−𝑓 𝑑2 𝑓−𝑓 𝑑2

And the fuzzy model is given in two rules as follows:

R1: If f(x) is Mf1 Then 𝑥̇ = 0


R2: If f(x) is Mf2 Then 𝑥̇ = 𝑑2 𝑥
Then
𝜇𝑅1 𝜇𝑅1 𝜇𝑅1
ℎ1 = 𝑟 = = = 𝑀𝑓1
∑1 𝜇𝑅𝑖 𝜇𝑅1 + 𝜇𝑅1 1
𝜇𝑅2 𝜇𝑅2
ℎ2 = 𝑟 = = 𝑀𝑔2
∑1 𝜇𝑅𝑖 1

The blended model after defuzzification is:

𝑥2
𝑥̇ = (ℎ1 𝑓 + ℎ2 𝑓)𝑥 = −𝑑2 ∙ 𝑥 = −𝑥 3
𝑑2

3
4
5
6
7
Example 2

Let 𝑥̇ = −𝑥 3 − 𝑥, 𝑥 ∈ [−𝑑, 𝑑]

Example 3

Let 𝑥̇ = 𝑥 3 −a(t)x, 𝑥 ∈ [−𝑑, 𝑑], 𝑎(𝑡) ∈ [0, 𝐾]

Example 4

Consider

𝑥̇ 1 = 𝑥1 𝑠𝑖𝑛𝑥1 − 4𝑥2

𝑥̇ 2 = −2𝑥1 𝑠𝑖𝑛𝑥1 − 2𝑥2


𝜋 𝜋
Where 𝑥 ∈ [− 2 , 2 ]

Example 5

Consider

𝑥̇ 1 = 𝑥2

𝑥̇ 2 = −(2 + 𝑔(𝑡))𝑥1 − 𝑥2

Where 𝑔(𝑡) ∈ [0, 𝐾]

Example 6

Consider

𝑥̇ = −𝑥 + 𝑥 3 + 𝑥𝑚 and 𝑥 ∈ [−𝑑, 𝑑]

Example 7

Consider

𝑥̇ = −𝑥 3 + 𝑥𝑚 and 𝑥 ∈ [−𝑑, 𝑑]

Example 8

Consider

𝜋 𝜋
𝑥̇ = 𝑥 2 𝑠𝑖𝑛𝑥 + (𝑥 + 2)𝑚 and 𝑥 ∈ [− , ] , 𝑠𝑖𝑛𝑥 ∈ [−1,1]
2 2